Circulating microRNAs as potential biomarkers in myasthenia gravis patients. Issue 1 (10th November 2017) - Punga, Anna Rostedt; Punga, Tanel
Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules that bind to specific mRNA targets and regulate a wide range of important biological processes within cells. Circulating miRNAs are released into the extracellular space and can be measured in most biofluids, including blood serum and plasma. Recently, circulating miRNAs have emerged as easily accessible markers in various body fluids with different profiles and quantities specific for different human disorders, including autoimmune diseases. In myasthenia gravis (MG), diagnostic tests such as titers of serum autoantibodies specific for either the acetylcholine receptor (AChR + ) or muscle‐specific tyrosine kinase (MuSK + ) do not necessarily reflect disease progression, and there is a great need for reliable objective biomarkers to monitor the disease course and therapeutic response. Recent studies in AChR + MG revealed elevated levels of the immuno‐miRNAs miR‐150‐5p and miR‐21‐5p. Of particular importance, levels of miR‐150‐5p were lower in immunosuppressed patients and in patients with clinical improvement following thymectomy. In MuSK + MG, another profile of circulating miRNAs was found, including upregulation of the let‐7 family of miRNAs. Here, we summarize the potential role of circulating miRNAs as biomarkers in general and in MG, and highlight important considerations for the analysis of circulating miRNA.